A Systematic Review of Applications of Prenatal Yoga Programs. (December 2016) - Kusaka, M.; Sugimoto, T.; Matsuzaki, M.; Haruna, M.
Abstract : Background: Prenatal yoga can improve the physical and psychological health of pregnant women. However, previous studies have often failed to describe the scientific rationale behind the structure of yoga programs. Objective: To summarize the characteristics of prenatal yoga programs in previous intervention studies and compare the structural differences between yoga programs. Methods: A systematic literature search was conducted to identify prenatal yoga interventions. The inclusion criteria of target articles were 1) written in English, 2) original article, 3) intervention study, 4) intervention included yoga poses, and 5) no intervention included other than yoga. Studies were classified based on yoga for healthy pregnant women and that for high-risk pregnant women with physical or mental disorders. Study design, participants, and details of yoga programs in terms of duration, frequency, period, and components were summarized. Results: Among 431 citations, 22 studies met the inclusion criteria. These studies were classified into 11 yoga intervention studies for healthy pregnant women and 11 studies for high-risk pregnant women. The majority of studies for healthy pregnant women adopted a yoga duration of more than 60 minutes. Half of the studies for healthy women utilized short, 6–8 week study periods and low frequency sessions, once or twice a week. In contrast, remaining studies for healthy women utilized long, 10–20 week study period and high-frequency sessions, three times a week. Most studies of high-risk pregnant women also adopted a yoga duration of more than 60 minutes. In contrast, three studies adopted a short duration of 20 minutes. The study period was 8–16 weeks and the frequency of yoga varied from once a week to three times a week. Conclusions: Prenatal yoga programs in previous studies varied considerably. Thus, careful interpretation of the literature is needed to apply prenatal yoga programs in clinical settings and research.